Les Catalans partagés entre le Roi et la Terre. Orthodoxie et hétérodoxie politiques autour de la révolte de 1640 - Mathias Ledroit (Nuevo mundo - Mundos Nuevos, 2009)
Before the Catalans’ revolt started in 1640 a « war of papers » between benafectes and malafectes was declared. The first shot came with the publication of the Proclamación Católica, which was an intent for its author to justify the Catalan ruling class’s policy against Madrid’s government. During the following months, this confrontation revealed that the Catalan society was deeply divided. This article aims at giving an interpretation of the main propaganda manifests and to show how the ideologues built the political orthodoxy that triumphed in 1641 when the Catalan ruling class decided to recognize Louis XIII’s authority. Yet their position weakened after the Count of Olivares fell into disgrace in 1643. Philipp IV’s supporters began encouraging the Catalan to put an end to a war they judged useless and disastrous and contesting the rebels’ political doctrine.